1999
DOI: 10.1111/1467-6494.00077
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Meanings of Religiousness and Spirituality: Problems and Prospects

Abstract: This article examines traditional and modern psychological characterizations of religiousness and spirituality. Three ways in which religiousness and spirituality are polarized by contemporary theorists are examined: organized religion versus personal spirituality; substantive religion versus functional spirituality; and negative religiousness versus positive spirituality. An alternative approach to understanding religiousness and spirituality is presented that integrates rather than polarizes these constructs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
462
1
22

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 719 publications
(492 citation statements)
references
References 69 publications
7
462
1
22
Order By: Relevance
“…In recent years, research has demonstrated that yoga may play a role in developing spiritual relationships. Spirituality, as a relationship construct, can be sought through relationships with a higher power, but also through the relationship with the self [19] [20] [21]. As a facet of spirituality, self-understanding seems to be an important for mental health care, stigma, and yoga [22].…”
Section: Body Mind Spirit Approachmentioning
confidence: 99%
“…In recent years, research has demonstrated that yoga may play a role in developing spiritual relationships. Spirituality, as a relationship construct, can be sought through relationships with a higher power, but also through the relationship with the self [19] [20] [21]. As a facet of spirituality, self-understanding seems to be an important for mental health care, stigma, and yoga [22].…”
Section: Body Mind Spirit Approachmentioning
confidence: 99%
“…When recognizing the different dimensions of "religion" and "spirituality", the understanding and definition of these phenomena is by nature complex and often these two are used interchangeably in the scientific research and clinical practice (Pargament, 1999;Zinnbauer, Pargament & Scott, 1999;Büssing et al, 2005;Koenig, King & Carson, 2012). This is essentially due to a great number of different perspectives, starting points and cultural contexts, as these terms can be seen as synonymous, overlapping, or completely different concepts (Hill et al, 2000;Tummala-Narra, 2009).…”
Section: Religion (Religiosity) and Spirituality: Relationship And Comentioning
confidence: 99%
“…However, one must also acknowledge they are not identical (Zinnbauer, et al, 1999) and for that reason conceptualisations that focus or are narrowed to certain aspects of religion or spirituality might not be appropriate (Saucier & Skrzypińska, 2006;Nelson, 2009).…”
Section: Religion (Religiosity) and Spirituality: Relationship And Comentioning
confidence: 99%
See 2 more Smart Citations